Monsoon‐Induced Zonal Asymmetries in Moisture Transport Cause Anomalous Pacific Precipitation Minus Evaporation. Issue 18 (21st September 2020) - Craig, P. M.; Ferreira, D.; Methven, J.
Abstract: Basin‐integrated precipitation minus evaporation ( P − E ) in the Pacific is near neutral while the Atlantic shows net evaporation. We link this P − E asymmetry to atmospheric moisture fluxes across the boundaries of the ocean drainage basins. Adopting an objective approach based on a comparison between actual fluxes and a zonally averaged circulation, we show that the asymmetry is dominated by moisture fluxes associated with the monthly mean flow at low latitudes rather than by differences in moisture fluxes into the Southern Ocean and Arctic catchments. In boreal summer, the eastward moisture flux, due to the Asian Summer Monsoon flow, opposes the zonal mean westward flux in the Trade Winds and results in more positive P − E over the Pacific than both the Atlantic and Indian Oceans, even in the annual mean. Our analysis reveals that moisture flux across Southeast Asia, rather than across Central America, is the dominant factor in the P − E asymmetry. Key Points: Atlantic and Pacific P − E (precipitation minus evaporation) asymmetry is primarily due to atmospheric moisture transport and precipitation Moisture fluxes into the polar ocean basins do not contribute notably to P − E asymmetries between the Atlantic, Pacific, and Indian basins Deviations from zonal mean zonal moisture flux associated with the summer monsoon flow across Southeast Asia dominate the P − E asymmetry